(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
The Siddha system is a traditional system of south India especially in Tamil Nadu. Thylam (medicated oil) is one of the 32 internal medicines. Karunkozhi thylam (KKT) is used to treat Vatha disease (degenerative disease). Qualitative and quantitative analysis ensures the quality and safety of drugs and minimizing contamination and adulteration risks. Weight/ml, refractive index (RI), density, iodine value (IV), acid value (AV) were analyzed as standardization parameter and GC-MS were employed to identify the active compound and test for heavy metals (lead, cadmium, mercury, arsenic), microbial contamination, test for specific pathogen (E.coli, Salmonella spp., Staphylococcus aureus, Pseudomonas aeruginosa), pesticide residue (organochlorine, organophosphorus, pyrethroids), test for Aflatoxins (B1, B2, G1, G2) were used as a safety measure. The result shows RI was 1.457, density was 1.213g/cm3, IV was 108.12g I/100g and AV was 0.86mg KOH/g. The safety parameters are within the acceptable limit. GC-MS shows the presence of oleic acid and n-hexodeconoeic acid that have anti-inflammatory activity. This study establishes a standardized protocol for KKT, ensuring quality, safety and efficacy. The findings have important implications for regulatory compliance and suggest areas for further research.